RELEVANSI PENDIDIKAN KARAKTER BERBASIS TAZKIYATUN NAFS DARI PEMIKIRAN HASAN AL-BANNA - Arief Maulana (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
The character crisis is a major challenge in modern education, especially amidst globalization and the moral decline affecting younger generations. Current character education models tend to emphasize cognitive and behavioral aspects while often neglecting the deeper dimension of spirituality. In this context, the concept of tazkiyatun nafs as introduced by Hasan al-Banna offers a comprehensive paradigm for character education. Tazkiyah refers not only to the purification of the soul but also to a transformative process of personality development through the cultivation of spiritual values such as sincerity, self-reflection (muhasabah), and commitment to universal goodness. This study adopts a qualitative approach using content analysis of Hasan al-Banna’s works, particularly his epistles that emphasize spiritual and educational themes. The researcher analyzes al-Banna’s philosophical framework on human nature as both a spiritual and social being, and how tazkiyah serves as the foundation for holistic educational reform. Findings show that tazkiyatun nafs can be effectively integrated into character education through a holistic approach that combines spiritual, emotional, and social dimensions. The implication of this study is the need for a paradigm shift in character education from merely shaping behavior to nurturing the soul in a comprehensive manner.